Initial experience of bamlanivimab monotherapy use in solid organ transplant recipients. Issue 5 (16th June 2021) - Kutzler, Heather L.; Kuzaro, Hillary A.; Serrano, Oscar K.; Feingold, Andrew; Morgan, Glyn; Cheema, Faiqa
Abstract: The widespread transmission of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) continues to propagate the coronavirus disease 2019 (COVID‐19) pandemic with solid organ transplant (SOT) recipients being an exceptionally vulnerable population for poor outcomes. Treatments for COVID‐19 are limited; however, monoclonal antibodies are emerging as a potential therapeutic option to change the trajectory of high‐risk patients. This retrospective single center cohort study evaluated the outcomes of SOT recipients with mild to moderate COVID‐19 who received bamlanivimab monotherapy. Eighteen SOT recipients (15 kidney, 2 liver, and 1 heart) received the medication between November 9, 2020 and February 10, 2021 with no reported infusion reactions. One patient experienced headache and fatigue following the infusion that resolved within 3 days. Fourteen patients continued their recovery as an outpatient with no further escalation in care. Three patients required hospitalization: two for suspected bacterial pneumonia 9 and 32 days postinfusion, respectively, and one for acute kidney injury 7 days postinfusion. One patient had an emergency room visit for gastrointestinal symptoms 24 days postinfusion. In this small cohort of SOT recipients, bamlanivimab monotherapy appeared to be a well‐tolerated option for treatment of mild to moderate COVID‐19, but it was not completely effective in preventing hospitalization. One month following the end of this cohort, COVID‐19 treatment guidance changed due to the rising prevalence of resistant variants. For this reason, bamlanivimab is now recommended to be used only in combination with etesevimab. Further studies are needed to fully elucidate the role of this therapy in SOT recipients.